Merger-induced metallicity dilution in cosmological galaxy formation simulations - Bustamente, Sebastian; Springel, Volker; Grand, Robert J. J. (Monthly notices of the Royal Astronomical Society, 2018)
ABSTRACT. Observational studies have revealed that galaxy pairs tend to have lower gas-phase metallicity than isolated galaxies. This metallicity deficiency ca
Gesehen am 01.02.2019